Long-term changes in tropical tree diversity : studies from the Guiana Shield, Africa, Borneo and Melanesia - ter Steege, H. (Tropenbos International WageningenNL, 2003)
Presents reports on a number of studies that take a long term view of forest disturbance and its effects on composition and diversity.